FORMULATION OF CINNAMON BARK ESSENTIAL OIL GEL AS MOSQUITO REPELLENT - KURNIAWAN, DHADHANG WAHYU; AGUSTINA, VIDYA NUR; SUNARTO; WIBOWO, GUNAWAN ADI; SYAMSU HIDAYAT, MUHAMMAD ZAENURI (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this research is to prepare a cinnamon bark essential oil gel preparation, determines the physical characteristic and physical stability during storage, and examines the activity of mosquito repellent from the best gel preparation. Methods: The formulations of gel were made with variations in the concentration of Carbopol 940 (0.5%, 1.5%, and 2%) contain 1% of cinnamon bark essential oil. The gel evaluated physical characteristics and physical stability. The parameters of organoleptic, homogeneity, and pH are analyzed descriptive, while the viscosity, the spreadability, and the gel adhesion were analyzed using one-way ANOVA at the level of confidence of 95%. The best gel tested its effectiveness as compared to the negative control and product innovator (which used DEET as an active compound) as a positive control. The activity of repellent was determined by an Aedes aegypti mosquito for 6 h with 2 hands respondents. The effectiveness of repellent protection is calculated by the percentage of protection power. Results: The studies showed that all the gel preparations qualified the organoleptic, homogeneity, and pH parameters. The viscosity, gel adhesion, and spreadability are also stable during storage. Conclusion: Based on the results, the best gel is the formula I which has mosquito repellent activity effective for 6 h like DEET.